Teen Mothers' Mental Health. Issue 1 (January 2016) - SmithBattle, Lee; Freed, Patricia
Abstract : ABSTRACT: Psychological distress is common in teen mothers. High rates of distress are attributed to teen mothers' childhood adversities and the challenges of parenting in the context of chronic stress, cumulative disadvantage, and limited social support. We describe the prevalence of psychological distress in teen mothers; what is known about its origins and impact on mothers and children; factors that promote teen mothers' mental health and resilience; and the many barriers that make it difficult to obtain traditional mental healthcare. We also briefly review the few studies that test interventions to improve teen mothers' mental health. Because barriers to traditional mental health treatment are ubiquitous and difficult to remedy, the second article in this two-part series calls for nurses in healthcare settings, schools, and home visiting programs to screen pregnant and parenting teens for adverse childhood experiences and psychological distress, and to integrate strength-based and trauma-based principles into their practice. Creating a supportive setting where past traumas and psychological distress are addressed with skill and sensitivity builds upon teen mothers' strengths and their aspirations to be the best parents they can be. These approaches facilitate the long-term health and development of mother and child. Abstract : Teen mothers often have psychological distress. High rates of distress are attributed to teen mothers' childhood adversities and the difficulties of parenting in the context of chronic stress, cumulative disadvantage, and limited social support.